Enhancemet and analysis of a hybrid liquid desiccant based-cooling system - Mahgoub, Elhadi Badawi (2007)
Air conditioning has traditionally been achieved by vapour compression equipment, which is considered very efficient when handling loads characterised by high sensible load fraction. These machines would perform poorly when they process air with high latent load fraction as in the case of humid climates. Global energy concern has accelerated the research on alternative technology options to replace traditional method or improve their performance. Hybrid liquid desiccant system has been proposed as an energy saving alternative to reduce the vapour compression unit size used in air conditioning application, and improve its performance. A hybrid system consisting of vapour compression unit, a liquid desiccant system consisting of an absorber and a regenerator, both of which are identical packed spray towers built from fibre glass with a cross sectional area of 600 x 600 mm from five pieces each. Each piece having a height of 200 mm to facilitate testing different heights of packing material, and a flat plate solar hot water collector with an auxiliary electrical heater to be used as supplement when solar energy is not enough or not available. This hybrid system was designed, fabricated and tested with emphasis on liquid desiccant sub-system. In this study, the performance of the absorber and the regenerator, which are the main items in the liquid desiccant system, was studied in terms of effectiveness. Both units were tested over a range of different inlet liquid desiccant concentration of 20% to 40% by weight, and inlet temperature of 20oC, 25oC, and 30oC for the absorber, and 20%, 25% and 30% liquid desiccant concentration at temperature range of 35oC to 55oC for the regenerator. Both components were tested at liquid desiccant flow rate between 3.76 to 5.01 l/min with different air inlet flow rate 4.9 to 6.4 m3/min. Experimental results were recorded using a complete data acquisition system to collect and log the data of the desiccant sub-system and the vapour compression unit, which enables thermocouples readings. From the data collected, the coefficient of performance of the vapour compression unit was obtained using both refrigerant enthalpy and air enthalpy methods. Absorber effectiveness was found to be between 0.5 and 0.7, while the regenerator effectiveness was found to be between 0.2 and 0.6. A 800 mm packing height is found to be the breaking limit with both air supply either fully through the desiccant or partly (50% through the desiccant), would result in an improvement in the performance of the vapour compression unit ranging from 17.9 % to 54%, which indicate the hybrid system potential for energy savings. Improving indoor air quality by controlling humidity, killing effect of bacteria and fungus by using liquid desiccant are among other benefits realised.